Changes in the integrity of thalamocortical connections are associated with sensorimotor deficits in children with congenital hemiplegia - Tsao, H.; Pannek, K.; Boyd, Roslyn; Rose, S. (2013)
Preservation of thalamocortical projections to the sensorimotor cortex is related to improved hand function in children with cerebral palsy (CP). Whether CP is associated with altered microstructure of these sensorimotor projections or other thalamocortical pathways remains unclear. Forty-two children with congenital hemiplegia and fifteen typically developing children (TDC) underwent structural and diffusion-weighted imaging (high-angular-resolution diffusion imaging) using a 3T MRI. Structural T1-images were parcellated into 34 cortical regions and the thalamus per hemisphere. Thalamocortical projections were extracted using probabilistic tractography and the top tan cortical regions with the greatest number of thalamocortical streamlines for the TDC group were selected for further analysis. The thalamus was parcellated based on its cortical connections. Differences between hemispheres for thalamocortical streamline numbers to each cortical region [asymmetry index (AI)], tract volume and tract microstructure [weighted mean fractional anisotropy (FA) and mean diffusivity (MD)] were calculated. Correlations between these measures (AI, FA and MD) and sensorimotor function were performed. Thalamocortical projections showed topographical organisation based on cortical connectivity. Projections to paracentral lobule, pre-central and post-central gyri showed greater AI in CP group, which indicates reduced streamlines on the ipsilesioned hemisphere. Reduced FA, reduced tract volume and increased MD were also found for these thalamocortical projections on the ipsilesioned hemisphere in children with CP. Changes in AI and tract microstructure of these projections were associated with poorer sensorimotor function. The findings suggest CP is associated with reorganisation of thalamocortical projections to the sensorimotor cortex. Integrity in these projections may underpin deficits in sensorimotor function.